Consumer Readiness for Microtransactions in Digital Content Business Models - Pankaj Chaudhary; Richelle Oakley DaSouza (Businesses)
As digital content increasingly moves away from free access, microtransactions may provide an alternative. There is a need for research on microtransactions as a general digital content payment mechanism. Businesses can capitalize on this technological advancement by expanding their paid digital content offerings without resorting to subscription-based services. This study examines a taxonomy for microtransactions based on consumer buying behavior, presents business models for microtransaction payment processing, and examines issues with its implementation. Data collected from 180 consumers were analyzed using quantitative and qualitative analyses to assess the receptiveness and perception of microtransactions. The results indicate that consumers are receptive to the concept of microtransactions and are willing to spend on five distinct digital content categories. This study concludes with a discussion of issues that consumers foresee with digital content microtransactions and implications for interested businesses.